A comparative plastomic analysis of Ziziphus jujuba var. spinosa (Bunge) Hu ex H. F. Chow and implication of the origin of Chinese jujube. Issue 2 (21st February 2023) - Du, Shuhui; Hu, Xiaoyan; Guo, Yuanting; Wang, Shengji; Yang, Xiuyun; Wu, Zhenzhen; Huang, Yuyin
Abstract: Comparative plastomics can be used to explicitly dissect various types of plastome variation. In the present study, the plastome variation pattern of Ziziphus jujuba var. spinosa (also called sour jujube) and its phylogenomic relationship with Chinese jujube were investigated. Plastomes of 21 sour jujube individuals were sequenced and assembled. The length of the sour jujube plastomes ranged between 159399 and 161279 bp. The plastomes exhibited collinearity of structure, gene order and content. The most divergent regions were located in the intergenic spacers, such as trnR-UCU - atpA and psbZ - trnG-UCC . Sliding window analysis demonstrated that the sequence variation among the sour jujube plastomes was relatively low. Sixty-two to 76 SSRs with 4 motif types were identified in the sour jujube plastomes with a predominant motif type of A/T. Three protein-coding genes exhibited higher nonsynonymous/synonymous substitution ratios, indicating that these genes may undergo positive selection. A total of 80 SNPs were detected and 1266 potential RNA editing sites of 23 protein-coding genes were predicted. In the phylogenomic tree constructed, sour jujube has a sister relationship to Chinese jujube, which indicates that Chinese jujube may have originated or been domesticated from sour jujube. The present study explicitly investigated the individual-level plastome variation of sour jujube and provides potential valuable molecular markers for future genetic-related study of this lineage.